Dual metronomic chemotherapy with nab-paclitaxel and topotecan has potent anti-angiogenic activity in ovarian cancer - Previs, Rebecca A. (Mol Cancer Ther, 2015)
There is growing recognition of the important role of metronomic chemotherapy in cancer treatment. On the basis of their unique anti-angiogenic effects, we tested the efficacy of nab-paclitaxel, which stimulates thrombospondin-1, and topotecan, which inhibits hypoxia-inducible factor 1-α, at metronomic dosing for the treatment of ovarian carcinoma. In vitro and in vivo SKOV3ip1, HeyA8, and HeyA8-MDR (taxane-resistant) orthotopic models were used to examine the effects of metronomic nab-paclitaxel and metronomic topotecan. We examined cell proliferation (Ki-67), apoptosis (cleaved caspase 3), and angiogenesis (microvessel density) in tumors obtained at necropsy. In vivo therapy experiments demonstrated treatment with metronomic nab-paclitaxel alone and in combination with metronomic topotecan resulted in significant reductions in tumor weight (62% in the SKOV3ip1 model, p < 0.01 and 96% in the HeyA8 model, p < 0.03) compared with vehicle (p < 0.01). In the HeyA8-MDR model, metronomic monotherapy with either cytotoxic agent had modest effects on tumor growth, but combination therapy decreased tumor burden by 61% compared with vehicle (p < 0.03). The greatest reduction in microvessel density (p <0.05) and proliferation was seen in combination metronomic therapy groups. Combination metronomic therapy resulted in prolonged overall survival in vivo compared to other groups (p < 0.001). Tube formation was significantly inhibited in RF-24 endothelial cells exposed to media conditioned with metronomic nab-paclitaxel alone and media conditioned with combination metronomic nab-paclitaxel and metronomic topotecan. The combination of metronomic nab-paclitaxel and metronomic topotecan offers a novel, highly effective therapeutic approach for ovarian carcinoma that merits further clinical development.